Opportunities for promoting open data in the Caribbean through biobanks - Sushant Saluja; Simon G. Anderson (Revista Panamericana de Salud Pública)
The establishment of a biobank in the Caribbean represents a vital opportunity to enhance biomedical research and tackle health issues in the area. The Caribbean’s unique genetic diversity, shaped by migration and environmental factors, underscores a well-managed biobank’s potential impact on global health, especially for underrepresented groups. This paper examines biobanking’s potential in the Caribbean, focusing on precision medicine, public health improvements and regional scientific self-sufficiency. It analyzes successful models such as the UK Biobank, the All of Us Research Program at the United States’ National Institutes of Health, and Human Heredity and Health in Africa (known as H3Africa), hosted at the University of Cape Town, pinpointing key lessons on data-sharing, ethical governance and infrastructure that could be applied to the Caribbean context. The UK Biobank and H3Africa are relevant examples due to their contributions to large-scale data and health research in diverse populations. The UK Biobank project is a large-scale study with deep genetic and phenotypic data from about 500 000 participants in the United Kingdom. It offers unprecedented insights into health data through extensive follow up and collection of genome-wide genotype data. H3Africa focuses on genomics research that addresses health disparities among African populations, which parallels the Caribbean’s challenges. Its ethical governance and community engagement focus are crucial for Caribbean biobank development. This article highlights the challenges of developing biobanks, including ensuring sufficient sample storage and data security, and the need for strong governance. It recommends solutions that involve regional collaboration, stakeholder engagement and increased investment in infrastructure. Establishing a Caribbean biobank with equitable data-sharing principles can significantly enhance global genomic data sets and ensure that the benefits of precision medicine reach the Caribbean. This study promotes a strategic, ethical and inclusive approach to biobanking for long-term success.